Non-epileptic psychogenic seizures: semiology in a patient’s cohort from a national reference epilepsy unit in Lima, Peru - Rodriguez-Vega, Oswaldo R. (2023)
Objective: To describe the semiology of Psychogenic Non-Epileptic Seizures (PNES) in patients diagnosed by video-electroencephalogram (VEEG) in a national epilepsy center. Methods: An observational, descriptive, and retrospective study of patients older than 14 years, admitted for telemetry monitoring at the Epilepsy Unit of the National Hospital Edgardo Rebagliati Martins in Lima, Peru, between January 1st, 2017, and December 31, 2022. A definitive diagnosis of PNES was reached through VEEG. Results: Twenty of 26 studied patients were female and 6 male. Most patients experienced loss of posture with falls (92%), gradual onset (88%), some degree of altered consciousness or responsiveness during the event (73%). The most prevalent motor signs included asynchronous movements of the trunk and/or extremities (73%), fluctuation in motor activity (73%), global or limb tremors (54%), and forced eyelid closure (50%). Non-motor signs were predominantly subjective symptoms (34%). Most of the patients presented motor PNES (73%) compared to non-motor (12%) and mixed (15%). Conclusions: The described clinical events had a prolonged duration, gradual onset, and altered levels of consciousness/responsiveness. The most frequent clinical motor signs were asynchronous movements of the trunk and/or extremities, motor fluctuation, tremors, and forced eyelid closure. Non-motor findings were, primarily, subjective symptoms. Most of the patients presented motor PNES.